Edukasi Media Untuk UMKM: Workshop Desain Konten Promosi Digital untuk UMKM Makanan Tradisional: Penelitian - Supriadi Supriadi; Raden Khaeru Ahmadi; Siti Saadah; Bondan Dewabrata; Rosnindar Prio Eko Rahardjo (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The development of digital media has created significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their product marketing reach. However, traditional food MSMEs in Sumenep Regency continue to face challenges in effectively utilizing digital media, particularly due to low media literacy, limited visual design skills, and insufficient understanding of digital promotional content strategies. This Community Service Program (Pengabdian kepada Masyarakat/PKM) aims to enhance the capacity of traditional food MSME actors in Sumenep through media literacy education and digital promotional content design workshops. The program employed a participatory-educative approach, including socialization, training sessions, hands-on practice in creating visual promotional content, discussions, and mentoring. The results indicate an improvement in participants’ understanding of the strategic role of digital media as a marketing tool, enhanced skills in producing more attractive and communicative visual content aligned with product characteristics, and a positive shift in attitudes toward viewing social media as a strategic business asset. Furthermore, the program strengthened participants’ confidence and creativity in promoting traditional food products based on local wisdom. Therefore, the integration of media literacy education and digital content design workshops proves to be an effective and sustainable assistance model in supporting the digital transformation of traditional food MSMEs in regional contexts.